Improved Survival after Resection of Liver and Lung Colorectal Metastases Compared with Liver-Only Metastases - Brouquet, Antoine (2011)
Background Lung metastases are considered a poor prognostic factor in patients with resectable colorectal liver metastases. Study Design We reviewed records of 1,260 consecutive patients with liver-only or liver-plus-lung (L+L) metastases from colorectal cancer who underwent resection with curative intent (1995 to 2009). Survival and prognostic factors were analyzed. Results There were 112 patients who underwent resection of L+L (mean 2 liver, 2 lung metastases). Mean tumor sizes were 3 cm and 1 cm, respectively. Thirty-four (31%) had bilateral lung metastases. Ten (9%) had synchronous L+L metastases, 60 (54%) had diagnosis of lung metastases within 1 year of liver resection. Most (108 of 112, 96%) had resection of liver before or at the same time as lung. Preoperative chemotherapy was used in 77 (69%) before liver resection and 56 (50%) before lung resection. Among L+L patients, no postoperative deaths occurred; postoperative morbidity rates were 26% after liver resection and 4% after lung resection. After a median of 49 months follow-up, L+L patients (n = 112) had better survival than liver only (n = 1,148) (5-year overall survival, L+L, 50% vs liver only, 40%; p = 0.01). CEA level > 5 ng/dL (hazard ratio [HR] 2.1, 95% CI 1.1 to 4.4, p = 0.04) and rectal primary (HR 2.9, 95% CI 1.4 to 6, p = 0.004) were associated with worse survival in L+L patients. Conclusions The survival rate for patients who undergo resection of L+L metastases from colorectal cancer is greater than the survival rate of the general population of patients who undergo resection of liver metastases only. The presence of resectable lung metastases is neither a poor prognostic factor nor a contraindication to resection of liver metastases.